2007
DOI: 10.1074/jbc.m608126200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-Hydroxy-2-nonenal Modification on α-Synuclein Aggregation

Abstract: Several observations have implicated oxidative stress and aggregation of the presynaptic protein ␣-synuclein in the pathogenesis of Parkinson disease. ␣-Synuclein has been shown to have affinity for unsaturated fatty acids and membranes enriched in polyunsaturated fatty acids, which are especially sensitive to oxidation under conditions of oxidative stress. One of the most important products of lipid oxidation is 4-hydroxy-2-nonenal (HNE), which has been implicated in the pathogenesis of Parkinson disease. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(169 citation statements)
references
References 56 publications
8
159
0
Order By: Relevance
“…It is known that lipid peroxidation and the 4-HNE level in SN increases in PD [49]. This increase intensifies the activation of caspases 3-8 what leads to apoptosis [50] and formation of a-synuclein aggregates [51]. In this study we found that the injection of MPTP increased nigral 4-HNE amount.…”
Section: Discussionsupporting
confidence: 61%
“…It is known that lipid peroxidation and the 4-HNE level in SN increases in PD [49]. This increase intensifies the activation of caspases 3-8 what leads to apoptosis [50] and formation of a-synuclein aggregates [51]. In this study we found that the injection of MPTP increased nigral 4-HNE amount.…”
Section: Discussionsupporting
confidence: 61%
“…HNE has also been found to induce oligomerization of aS and cause toxicity to dopaminergic neurons in vitro (49). Similar to 4-oxo-2-nonenal and HNE, DOPAL can form covalent adducts with aS via MA and SB reactions (50), which target Lys residues.…”
Section: Discussionmentioning
confidence: 99%
“…An important issue is to understand whether these chemical modifications are a requirement for the aggregation process. In the presence of lipids and fatty acids, these types of modifications, such as protein oxidations and aliphatic carbonyl adducts formation, have been observed both in vivo and in vitro (18,43,44). They are generated by radicals, hydroperoxides, and successively highly reactive aldehydes, produced by peroxidation of lipids.…”
Section: Tablementioning
confidence: 99%
“…Moreover, in vitro studies have shown that the lipid oxidation product, 4-hydroxy-2-nonenal, covalently binds to ␣-syn. As a consequence, ␣-syn can no longer form fibrils but only oligomeric species, which have been suggested to contribute to the damage of neurons subjected to oxidative stress (18). However, it was found that ␣-syn can act as scavenger of ROS, preventing unsaturated lipids oxidation in vesicles by the oxidation of the methionine residues to methionine-sulfoxide (19).…”
mentioning
confidence: 99%